Revolutionizing Insurance Industry with The Aspects of Business Intelligence - Seethal keloth, S. Poorani Mithila, Dr. B. Menaka (International Journal of Advanced Science and Technology, 2020)
In recent years, the effort for improving the standards of insurance industry and insurance business are at huge pace with a huge investment at stake, yet the struggle remains the same because of the negligence to see the bigger picture, that is ‘their approach to data’. Insurance companies are facing a constant invasion of actuarial data, claims data, market data, consumer data and so on.It is inevitable for insurance industry to seek the affirmatives of business intelligence, asthe aspects of it has not benefited the insurance industry so far, even though it is the leading sector in utilizing the benefits of business intelligencecompared to the other sectors such as hospitality, financial services and health care. Insurance companies must formulate dash boards, data discovery, reporting, data mining, end user self- service and data warehousing with regards to business intelligence. Self-service business intelligence tools are now provided by analytics software vendors who offer business intelligence tools, some of the vendors include Birst, Domo, Google, Microsoft, IBM, Salesforce, SAP, Qlik, Tableau and Sisense.  Keyword:.  Business intelligence, optimal decisions, self-service, insights, claims, fraud.